2016
DOI: 10.1136/bmjopen-2016-011755
|View full text |Cite
|
Sign up to set email alerts
|

Patients' estimations of the importance of preventive health services: a nationwide, population-based cross-sectional study in Portugal

Abstract: ObjectivesTo determine, in the context of primary care preventive health services, the level of importance that Portuguese patients attribute to different preventive activities.DesignCross-sectional study.SettingPrimary Healthcare, Portugal.Participants1000 Portuguese adults selected by a stratified cluster sampling design were invited to participate in a computer-assisted telephone survey. Persons with a cognitive or physical disability that hampered the ability to complete a telephone interview and being a n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
14
0
5

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 24 publications
(57 reference statements)
1
14
0
5
Order By: Relevance
“…A similar pattern was found in test ordering in other general practice studies, 15 18 and the Eurosentinel Study Group showed that haemogram and glucose were the most frequently requested laboratory tests in eight countries. 1 These results are consistent with the expectations of Portuguese patients, who consider that ‘routine blood and urine tests’ are the most important preventive medical activities, 22 with a mean frequency interval of 12 months. 3 This test is popular among Portuguese people in their periodic health examinations or routine health check-ups.…”
Section: Discussionsupporting
confidence: 82%
“…A similar pattern was found in test ordering in other general practice studies, 15 18 and the Eurosentinel Study Group showed that haemogram and glucose were the most frequently requested laboratory tests in eight countries. 1 These results are consistent with the expectations of Portuguese patients, who consider that ‘routine blood and urine tests’ are the most important preventive medical activities, 22 with a mean frequency interval of 12 months. 3 This test is popular among Portuguese people in their periodic health examinations or routine health check-ups.…”
Section: Discussionsupporting
confidence: 82%
“…A maioria dos portugueses consideram que devem efetuar AR ao sangue e urina, com uma frequência média de 12 meses. 13 Com este estudo verificou-se que mais de metade dos médicos ainda prescreve AR, o que não está de acordo com as recomendações atuais que defendem não existir benefício (mas sim um potencial aumento do risco de causar dano) para o doente na requisição de AR. 6 Impôs-se a necessidade de realizar um estudo qualitativo para apurar os motivos que levam à manutenção desta má prática nomeadamente explorar se existe uma perversão da relação médico--doente na qual o médico não tenha poder para fazer face a questões culturalmente instituídas.…”
Section: Discussionunclassified
“…O desafio é lançado, para a criação de estratégias de marketing social para mudar a cultura vigente no sentido de reduzir o risco público associado a sobre-utilização, sobrediagnóstico e sobretratamento que a realização inapropriada de exames acarreta. 13…”
Section: Conclusãounclassified
“…Miguel BIGOTTE VIEIRA* 1,2,3 , Guilherme FERREIRA-DOS-SANTOS* 2,3,4 , Catarina Reis de CARVALHO 2,5 , Catarina Viegas DIAS 2,6 , David Cordeiro SOUSA 2,7 , Inês LEAL 2,7 , João VALENTE JORGE 2,8 , Mariana ALVES 2,9 , Mariana MORGADO 2,10 , Rute Baeta BAPTISTA 2,11 , Paula FORTUNATO 12 , António VAZ-CARNEIRO 2,3 , Miguel GUIMARÃES 12,13 Acta Med Port 2018 Oct;31(10):521-523 ▪ https://doi.org/10.20344/amp.11138…”
unclassified
“…Estas convicções conduzem à solicitação frequente destas intervenções ao profissional de saúde. 4 A implementação deste programa em Portugal pretende promover escolhas criteriosas em saúde e facilitar a comunicação entre profissionais de saúde e doentes.…”
unclassified